(499) An Appraisal of the Animal Production projects of The First Five-Year's Plan of Agricultural Development in the U.A.R تقييم مشاريع الإنتاج الحيواني في الخطة الخمسية الأولى للتنمية الزراعية في جمهورية أرمينيا الاتحادية - Mohamed Ibrahim Abd-El- Ghani (Institute of National Planning, 2025)
This study examines the evaluation of animal and aquatic wealth projects within the framework of economic development planning, with particular emphasis on their effectiveness in meeting production and development objectives. The study highlights the growing imbalance between domestic production and increasing demand for animal and fish products, which contributed to food shortages and greater dependence on imports. Consequently, development authorities incorporated animal and fishery projects into national economic development plans. The study adopts an analytical and evaluative approach to assess project implementation efficiency and the degree of consistency between project outcomes and planned targets. Findings indicate that many projects were approved without sufficient technical and economic feasibility studies, resulting in implementation delays and limited achievement of planned objectives. In addition, time priorities and implementation sequences were often poorly designed, with some projects requiring significantly longer implementation periods than initially projected. The study further identifies institutional and administrative problems related to assigning implementation responsibilities to agencies whose functions were not fully aligned with project requirements. The implementation rate of aquatic wealth projects was particularly weak because of shortages in foreign exchange required for importing vessels, motors, and fishing equipment. Actual investment expenditures represented only a very small proportion of planned expenditures, indicating poor implementation performance. The analysis also highlights deficiencies in pricing policies, financial support mechanisms, and statistical follow-up systems. Existing pricing policies were not based on actual production costs and therefore failed to provide incentives for producers. Financial resources allocated to animal production projects were insufficient, while inadequate statistical monitoring limited the ability to assess project performance accurately. Furthermore, policies concerning lake drainage and land reclamation contributed to reductions in Egyptian lake areas and negatively affected fish production. The study concludes that improving the effectiveness of animal and aquatic wealth projects requires comprehensive feasibility studies, stronger monitoring and evaluation systems, improved financing mechanisms, more effective pricing policies, and better institutional coordination to ensure sustainable economic development.